Negative electrode material of lithium ion battery and preparation method of negative electrode material
By using a combined structure of porous matrix, conductive carbon material and cladding layer in the negative electrode material of lithium-ion battery, the performance degradation caused by volume expansion during charging and discharging of silicon-based materials is solved, and the electrochemical performance and prolonged cycles are achieved. Lifespan effect.
Patent Information
- Application Number
- CN202411686703.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-14
AI Technical Summary
The volume expansion of the silicon-based anode material during charging and discharging of lithium-ion batteries causes material rupture, and the reconstruction of SEI film accelerates lithium ion consumption and material powdering, affecting its capacity and electrochemical properties.
Using a negative electrode material structure consisting of a porous substrate, conductive carbon material and a cladding layer, the pores of the porous substrate provide space for the volume expansion of silicon, the conductive carbon material is embedded in the pores and coated on the surface, and the cladding layer prevents the conductive carbon material from falling off and Enhance overall conductivity.
It reduces the damage to the material by volume expansion of silicon, improves the conductivity and electrochemical properties of the negative electrode material, and extends the cycle life of lithium-ion batteries.
Smart Images

Figure CN119447264A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a negative electrode material of a lithium-ion battery and a preparation method thereof. Background Art
[0002] With the rapid development of society, new energy vehicles, power tools, electronic products, etc. require lithium-ion batteries with higher energy density. The capacity of traditional graphite negative electrode materials is close to the theoretical capacity and it is difficult to meet the high energy density requirements. The theoretical capacity of silicon negative electrode materials can reach 4200mAh / g, and it has the advantages of rich reserves and a discharge platform similar to graphite. It is considered to be the next generation of lithium-ion battery negative electrode materials with great development potential.
[0003] However, during the charge and discharge process, silicon has a volume expansion of >300%. The huge stress will not only cause the material particles to rupture, the reconstruction of the SEI film accelerates the consumption of lithium ions, but also cause the material to pulverize, seriously affecting its capacity and electrochemical performance. In addition, silicon negative electrode materials also have the defect of low electrical conductivity, which limits the practical application of silicon as a negative electrode material for lithium-ion batteries. Summary of the invention
[0004] The present application provides a negative electrode material for a lithium-ion battery and a preparation method thereof, so as to improve the technical problems of volume expansion and poor conductivity of silicon-based negative electrode materials, and to improve the electrochemical performance of lithium-ion batteries.
[0005] The technical solutions for this application are as follows:
[0006] In a first aspect, the present application provides a negative electrode material for a lithium-ion battery. The negative electrode material comprises, from the inside to the outside, a porous matrix, a conductive carbon material and a coating layer.
[0007] The porous matrix is made of silicon, silicon alloy or silicon oxide. The porous matrix includes a plurality of pores, at least part of which are open on the surface of the porous matrix.
[0008] Part of the conductive carbon material is located on the surface of the porous matrix, and part of the conductive carbon material is located in the pores of the porous matrix.
[0009] The coating layer has ionic conductivity and / or electronic conductivity, and wraps the entirety of the porous matrix and the conductive carbon material.
[0010] Based on the lithium-ion battery negative electrode material provided in the first aspect, the pores of the porous matrix provide a certain space for the volume expansion of silicon during the charge and discharge process, and the conductive carbon material embedded in the pores and coated on the surface of the porous matrix enhances the conductivity inside and outside the silicon particles, and the conductive carbon material layer on the surface also plays a role in buffering the volume expansion of silicon to a certain extent. The outermost layer of the negative electrode material can trap the conductive carbon material on the surface of the porous matrix, effectively preventing the conductive carbon material from falling off, further inhibiting the volume expansion of silicon, and improving its electrochemical performance.
[0011] Therefore, the lithium-ion battery negative electrode material provided in the present application can reduce the damage caused by the volume expansion of silicon to the material when silicon materials, silicon alloy materials, and silicon oxide materials are used as negative electrode materials, and can also improve the conductivity of the negative electrode material, thereby improving the electrochemical performance of the silicon-based negative electrode material.
[0012] In one possible design, the covering layer is in the form of a film or a mesh.
[0013] Based on the negative electrode material of the lithium-ion battery provided in this embodiment, when the coating layer is in a film or mesh shape, the coating layer has a relatively good coating force, so it can play a better role in preventing the conductive material from falling off.
[0014] In a possible design, the coating layer is in the form of a film, and the material of the coating layer is cyclized polyacrylonitrile. The cyclized polyacrylonitrile has good electrical conductivity, which can prevent the conductive carbon material from falling off and enhance the electrical conductivity of the negative electrode material.
[0015] In a possible design, the size of the porous matrix is in the micrometer range, the pore diameter is greater than 100 nanometers and less than 300 nanometers, and the diameter of the conductive carbon material is less than 100 nanometers.
[0016] Based on the negative electrode material of the lithium ion battery provided by this embodiment, the size of the porous matrix is micrometer-level, the diameter of the pore is greater than 100 nanometers and less than 300 nanometers, and the diameter of the conductive carbon material is less than 100 nanometers. In this way, the porous matrix can have a certain structural stability, and the conductive carbon material can be inserted into the pores, so that the conductivity of the porous matrix can be improved from the inside of the porous matrix. In addition, there is a gap between the pores and the conductive carbon material, which can not only alleviate the volume expansion of silicon, but also facilitate the infiltration of the porous matrix by the electrolyte.
[0017] In one possible design, the conductive carbon material is carbon nanospheres.
[0018] Based on the negative electrode material of the lithium-ion battery provided in this embodiment, the carbon nanospheres have the characteristics of good conductivity, easy acquisition of raw materials, and low calcination temperature. This facilitates the improvement of the conductivity of the negative electrode material and has low cost.
[0019] In the second aspect, based on the same inventive concept, the present application also provides a method for preparing a negative electrode material for a lithium ion battery, comprising the following steps:
[0020] A porous substrate is provided, wherein the porous substrate comprises a plurality of pores, and at least part of the pores are open to the surface of the porous substrate.
[0021] A conductive carbon material is formed on the surface and pores of the porous matrix.
[0022] The coating layer is wrapped on the surface of the integral structure formed by the porous matrix and the conductive carbon material, and the coating layer has ionic conductivity and / or electronic conductivity.
[0023] The lithium-ion battery negative electrode material of the first aspect can be produced by the preparation method of the lithium-ion battery negative electrode material provided in the second aspect. In this way, the lithium-ion battery negative electrode material of the first aspect also has the beneficial effects of the lithium-ion battery negative electrode material provided in the first aspect, which will not be described in detail here.
[0024] In one possible design, the preparation of the conductive carbon material includes the following steps:
[0025] The carbon source, structure directing agent and dispersant are dissolved to form a solution.
[0026] A porous matrix is added to the solution, and the solution is distributed in the pores and surface of the porous matrix.
[0027] The carbon source in the solution is carbonized under the action of the structure directing agent to generate monodisperse carbon balls.
[0028] The calcination conditions are controlled to carbonize the carbon balls to form conductive carbon materials.
[0029] Based on the method for preparing the negative electrode material of a lithium-ion battery provided in this embodiment, during the preparation process of the conductive carbon material, due to the fluidity of the solution, the solution can easily enter the deep pores of the porous matrix. In this way, a conductive carbon material can be formed deep in the pores of the porous matrix, thereby helping to improve the conductivity of the porous matrix from the inside out.
[0030] In a possible design, the carbon source is one of glucose, maltose, sucrose and soluble starch.
[0031] The structure directing agent is one of polyquaternary ammonium salt, polymethacrylamide propyl trimethyl ammonium chloride and polydiallyl dimethyl ammonium chloride.
[0032] In one possible design, the porous substrate is a porous silicon substrate, and the formation of the porous silicon substrate includes the following steps:
[0033] Micron-sized silicon powder is treated with a mixed solution of AgNO3 and HF to obtain silver-deposited silicon particles.
[0034] Silicon particles with Ag particles on the surface are treated with a mixed solution of H2O2 and HF to obtain a porous silicon matrix.
[0035] Based on the method for preparing the negative electrode material for a lithium-ion battery provided in this embodiment, pores are created on silicon powder by using AgNO3, HF, and H2O2. This method is simple and easy to implement.
[0036] In one possible design, the coating layer is cyclized polyacrylonitrile. The preparation of the coating layer includes the following steps:
[0037] The polyacrylonitrile and the porous matrix containing the conductive carbon material are placed in an N,N-dimethylformamide solvent, and heated and stirred to uniformly mix the polyacrylonitrile and the conductive carbon material in the solvent.
[0038] Afterwards, the mixed solution is post-treated to obtain a mixed powder, and the mixed powder is calcined under the protection of an inert gas to cyclize the polyacrylonitrile, thereby encapsulating the overall structure formed by the conductive carbon material and the porous matrix.
[0039] Based on the method for preparing the negative electrode material of a lithium-ion battery provided in this embodiment, the polyacrylonitrile prepared by the above steps is distributed relatively evenly on the surface of the overall structure formed by the porous silicon and the conductive carbon material, thus playing a good role in preventing the conductive carbon material from falling off. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The negative electrode material prepared in Example 1 and the negative electrode material prepared in Comparative Example 1 are respectively assembled into CR2025 type button batteries, and the capacity retention rate comparison chart after 50 cycles is shown.
[0041] Figure 2 This is an EIS comparison chart of the negative electrode material prepared in Example 1 and the negative electrode material prepared in Comparative Example 1 assembled into CR2025 type button cells after 2 weeks of charge and discharge. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0043] The embodiments given in this application can be combined with each other without any contradiction. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0044] All raw materials used in this application have no particular limitation on their sources and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0045] All raw materials used in the present application, unless otherwise specified, are raw materials commonly used in the art, and those skilled in the art can purchase them commercially or prepare them using conventional methods based on the names of the raw materials and their corresponding uses.
[0046] The abbreviations of the processes used in this application are all conventional abbreviations in the field. The specific steps and conventional parameters of each abbreviation are clear and definite in its relevant field, and those skilled in the art can implement them in a conventional manner based on the abbreviations.
[0047] Unless otherwise defined, all terms used herein have the same meanings as commonly understood by those skilled in the art unless otherwise specified.
[0048] The following is a detailed description of this application.
[0049] As described in the background art, during the charge and discharge process of lithium-ion batteries, silicon has problems of volume expansion and poor conductivity, which affects the electrochemical properties of silicon.
[0050] Based on this, the present application provides a negative electrode material for a lithium-ion battery, which includes a porous matrix, a conductive carbon material and a coating layer from the inside to the outside.
[0051] The porous matrix is made of silicon, silicon alloy or silicon oxide. The porous matrix includes a plurality of pores, at least part of which are open on the surface of the porous matrix.
[0052] Part of the conductive carbon material is located on the surface of the porous matrix, and the other part is located in the pores of the porous matrix.
[0053] The coating layer has ionic conductivity and / or electronic conductivity, and wraps the entirety of the porous matrix and the conductive carbon material.
[0054] The silicon, silicon alloy or silicon oxide mentioned in this application are all used in the negative electrode of the field of lithium-ion batteries, wherein silicon alloy is a composite material formed by alloying silicon with one or more metal elements (such as tin, aluminum, nickel, cobalt, etc.). Silicon oxide SiOx refers to a compound formed by silicon and oxygen in different proportions, wherein the value of x is generally between 1 and 2. Common silicon oxygen materials include SiO, SiO2, etc. Among them, the volume expansion of silicon during charging and discharging is the largest, and the volume expansion of silicon alloy or silicon oxide during charging and discharging is relatively small.
[0055] In some embodiments of the present application, the pores include pores opened on the surface of the porous matrix. In other embodiments of the present application, the pores of the porous matrix also include pores inside the porous matrix.
[0056] The negative electrode material provided in the present application includes a porous matrix. The pores of the porous matrix provide a buffer space for the volume expansion of the negative electrode material during the charge and discharge process, which can reduce the stress caused by the volume expansion and improve the structural stability of the negative electrode material.
[0057] The negative electrode material of the present application also includes a conductive carbon material, part of which is located in the pores, and the other part of which is located on the surface of the porous matrix. In this way, the conductive carbon material not only exists on the surface of the porous matrix, but also penetrates into the interior of the porous matrix. This structure helps to improve the conductivity of the negative electrode material from the inside out.
[0058] The negative electrode material of the present application also includes a wrapping layer, which wraps the entire structure composed of the porous matrix and the conductive carbon material, and its purpose is to prevent the conductive carbon material from falling off during the charge and discharge process. In addition, the wrapping layer has ionic conductivity and / or electronic conductivity, and to a certain extent can form a conductive network on the surface of the entire structure composed of the porous matrix and the conductive carbon material, further improving the conductivity of the negative electrode material.
[0059] From the above, it can be seen that the lithium-ion battery negative electrode material provided in the present application can reduce the damage caused by the volume expansion of silicon to the material when silicon materials, silicon alloy materials, and silicon oxide materials are used as negative electrode materials, and can also improve the conductivity of the negative electrode material, thereby improving the electrochemical performance of the silicon-based negative electrode material.
[0060] In some embodiments of the present application, the coating layer is in the form of a film or a mesh. Specifically, one of the main functions of the coating layer in the present application is to prevent the conductive carbon material from falling off. When the coating layer is in the form of a film or a mesh, the coating layer has a relatively good coating force, so it can better prevent the conductive material from falling off.
[0061] It should be noted that in the application, the thickness of the coating layer should be appropriate. Generally speaking, if the coating layer is too thin, it will lead to incomplete coating and fail to effectively prevent the conductive carbon material particles from falling off. However, if the coating layer is too thick, the ion transmission path will become longer and the impedance will increase. Therefore, it is necessary to control the coating amount during the preparation of the negative electrode material.
[0062] In some embodiments of the present application, the coating layer is in the form of a film, and the material of the coating layer is cyclized polyacrylonitrile. The cyclized polyacrylonitrile has good electrical conductivity, which can prevent the conductive carbon material from falling off and enhance the electrical conductivity of the negative electrode material.
[0063] It should be noted that the material of the coating layer is cyclized polyacrylonitrile, which is only one embodiment of the present application. In other embodiments of the present application, other materials may also be selected, such as graphene and carbon nanotubes.
[0064] In some embodiments of the present application, the size of the porous matrix is micrometer-sized, the diameter of the pores is greater than 100 nanometers and less than 300 nanometers, and the diameter of the conductive carbon material is less than 100 nanometers.
[0065] Specifically, the size of the porous matrix cannot be too large or too small. If the size of the porous matrix is too small, then based on the existing process, it is not convenient to make pores on the porous matrix. Or after the pores are made on the porous matrix, the structure of the porous matrix itself is prone to collapse. If the size of the porous matrix is too large, it will also affect the preparation of the negative electrode sheet. Taking all factors into consideration, the size of the porous matrix of the present application is at the micron level.
[0066] Based on similar reasons as mentioned above, the size of the pores should not affect the structural stability of the porous matrix on the one hand, and should be able to accommodate the conductive carbon material on the other hand. Therefore, based on comprehensive considerations, the size of the pores in this application is greater than 100 nanometers and less than 300 nanometers.
[0067] In the present application, the diameter of the conductive carbon material is less than 100 nanometers, so there is a certain gap between the conductive carbon material and the pores. This gap has the following two functions:
[0068] First, during the charge and discharge process of lithium-ion batteries, the gap between the conductive carbon material and the pores can provide a buffer space for the volume expansion of silicon, reduce the stress in the negative electrode material, avoid the tearing of the SEI film, and the pulverization of the negative electrode material. Second, the gap can serve as a channel for the electrolyte of the lithium-ion battery, facilitating the infiltration of the electrolyte into the porous matrix.
[0069] In some embodiments of the present application, the conductive carbon material is carbon nanospheres. The present application selects carbon nanospheres because they have good electrical conductivity, easy access to raw materials, and low calcination temperature. It should be noted that the selection of carbon nanospheres as the conductive material is only one embodiment of the present application. In some other embodiments of the present application, the conductive carbon material may also be graphene nanospheres or carbon nanotube nanospheres that meet the particle size requirements.
[0070] Based on the same inventive concept, the present invention also provides a method for preparing a negative electrode material for a lithium ion battery, comprising the following steps:
[0071] A porous substrate is provided, wherein the porous substrate comprises a plurality of pores, and at least part of the pores are open to the surface of the porous substrate.
[0072] A conductive carbon material is formed on the surface and pores of the porous matrix.
[0073] The coating layer is wrapped on the surface of the integral structure formed by the porous matrix and the conductive carbon material, and the coating layer has ionic conductivity and / or electronic conductivity.
[0074] The method for preparing the negative electrode material for a lithium-ion battery provided by the present invention can produce the negative electrode material for a lithium-ion battery of the first aspect, thus having the beneficial effects of the negative electrode material for a lithium-ion battery, which will not be described in detail here.
[0075] In some embodiments of the present application, the preparation of the conductive carbon material comprises the following steps:
[0076] S1) dissolving the carbon source, structure directing agent and dispersant to form a solution.
[0077] S2) A porous matrix is added to the solution, and the solution is distributed in the pores and surface of the porous matrix.
[0078] S3) causing the carbon source in the solution to undergo a carbonization reaction under the action of the structure directing agent to generate monodispersed carbon spheres.
[0079] S4) controlling the calcination conditions to carbonize the carbon balls to form a conductive carbon material.
[0080] It can be seen from step S1) that when preparing the conductive carbon material, the present application first dissolves the reactants, structure directing agent and dispersant of the conductive carbon material to form a solution, wherein the dispersant and structure directing agent serve to guide and control the reactants to form uniform and size-controlled carbon balls during the subsequent reaction. In some embodiments of the present application, the structure directing agent and the dispersant may be the same substance.
[0081] In step S2), a porous matrix is added to the solution. Thus, due to the fluidity of the solution, the solution can enter the pores of the porous matrix. Thus, the same concentration of solution will exist in the pores and surface of the porous matrix.
[0082] It can be seen from the above steps that in the preparation process of conductive carbon materials, due to the fluidity of the solution, the solution can easily enter the deep pores of the porous matrix. In this way, conductive carbon materials can be formed deep in the pores of the porous matrix, which helps to improve the conductivity of the porous matrix from the inside out.
[0083] It should be noted that, in the present application, the size of the conductive carbon material can be controlled by the amount of structure directing agent added and the calcination conditions.
[0084] In some embodiments of the present application, the carbon source is one of glucose, maltose, sucrose and soluble starch.
[0085] The structure directing agent is one of polyquaternary ammonium salt, polymethacrylamide propyl trimethyl ammonium chloride and polydiallyl dimethyl ammonium chloride.
[0086] In some embodiments of the present application, the porous substrate is a porous silicon substrate, and the formation of the porous silicon substrate comprises the following steps:
[0087] Micron-sized silicon powder is treated with a mixed solution of AgNO3 and HF to obtain silver-deposited silicon particles.
[0088] Silicon particles with Ag particles on the surface are treated with a mixed solution of H2O2 and HF to obtain a porous silicon matrix.
[0089] The chemical reactions that occur in the process of obtaining silver-deposited silicon particles are as follows:
[0090] Si(s)+4AgNO3+6HF→H2SiF6+4Ag+4HNO3.
[0091] The chemical reaction between H2O2 and HF and silicon particles is as follows:
[0092] Si+n / 2H2O2+6HF→nH2O+H2SiF6+(4-n) / 2H2↑.
[0093] In the process of forming pores on the surface of micron-sized silicon powder, Ag mainly plays a catalytic and positioning role. That is to say, at the position where Ag particles are attached to the surface of silicon particles, silicon easily reacts with H2O2, and the resulting product reacts with HF to generate soluble H2SiF6, which in turn generates corresponding pores in the silicon powder and obtains a porous silicon matrix.
[0094] It should be noted that when the porous silicon substrate is formed by the above method, the size of Ag particles can be controlled by adjusting the concentration of AgNO3 to adjust the C HF / (C H2O2 +C HF ) The molar concentration ratio controls the reaction rate and etching direction, and the pore size is controlled by adjusting these two factors.
[0095] It should be noted that the preparation of the porous silicon substrate provided in this application is only one of the methods for preparing porous silicon. The porous silicon substrate mentioned in this application can also be prepared by other existing methods, such as: anodization method, laser etching method, photolithography method. The porous silicon substrate of this application can also be obtained by purchase.
[0096] In one embodiment of the present application, the coating layer is cyclized polyacrylonitrile. The preparation of the coating layer comprises the following steps:
[0097] The polyacrylonitrile and the porous matrix containing the conductive carbon material are placed in an N,N-dimethylformamide solvent, and heated and stirred to uniformly mix the polyacrylonitrile and the conductive carbon material in the solvent.
[0098] Afterwards, the mixed solution is post-treated to obtain a mixed powder, and the mixed powder is calcined under the protection of an inert gas to cause polyacrylonitrile to undergo cyclization and be coated on the surface of the integral structure formed by the conductive carbon material and the porous matrix.
[0099] The polyacrylonitrile prepared through the above steps is distributed relatively evenly on the surface of the overall structure formed by the porous silicon and the conductive carbon material, thus playing a good role in preventing the conductive carbon material from falling off.
[0100] It should be noted that the present application provides a specific method for preparing a coating layer. Based on the core idea of the present application, the coating layer of the present application can also select other materials. Different materials will result in different coating methods. After understanding the role of the coating layer of the present application, those skilled in the art are capable of selecting suitable coating materials and selecting appropriate coating methods. Therefore, the polyacrylonitrile after cyclization mentioned in the present application is only an example of the present application and is not intended to limit the present application.
[0101] For example, as mentioned above, the material of the coating layer, in addition to the cyclized polyacrylonitrile, can also be other film-like or mesh-like materials, such as graphene or carbon nanotubes.
[0102] As for carbon nanotubes, since carbon nanotubes are tubular materials, a plurality of carbon nanotubes in contact will form a network structure. Thus, when carbon nanotubes are used as a coating material, it is only necessary to physically mix the carbon nanotubes with porous silicon containing a conductive carbon material.
[0103] For graphene, a uniformly dispersed graphene oxide solution is ultrasonically mixed with a porous silicon matrix containing a conductive carbon material, and then subjected to processes such as drying and high-temperature sintering to obtain a graphene-coated negative electrode material.
[0104] The negative electrode material of the lithium ion battery provided by the present application is described in detail above, and the preparation method of the lithium ion battery is described in detail. The effect of the present application is verified by specific examples below.
[0105] Embodiment 1:
[0106] 1) Preparation of porous silicon substrate
[0107] 1.1) The micron-sized silicon powder raw material is subjected to ultrasonic and centrifugal cleaning treatment with deionized water and anhydrous ethanol, and then vacuum dried to remove impurities in the silicon powder.
[0108] 1.2) Prepare 200 mL of a mixed solution containing 0.02 mol / L AgNO3 and 2 mol / L HF, add 2 g of the silicon powder treated in step 1.1) to the mixed solution, react for 3 min under rapid stirring, and then wash with deionized water and vacuum dry to obtain Ag-deposited silicon particles.
[0109] 1.3) Prepare 200 mL of a mixed solution containing 0.05 mol / L H2O2 and 0.15 mol / L HF. Add silicon particles with Ag particles on the surface to the mixed solution, react for 30 minutes, wash with deionized water, and vacuum dry to obtain a porous silicon substrate, denoted as Si.
[0110] 2) Formation of carbon nanospheres on the surface and in the pores of the porous silicon substrate
[0111] 2.1) Weigh 10 g of glucose and 0.16 g of polyquaternium-11 into 50 mL of deionized water, stir and dissolve at room temperature for 30 min, then add 1 g of the porous silicon substrate prepared in step 1), and continue stirring at room temperature for 2 h.
[0112] 2.2) The mixture obtained in step 2.1) was transferred to a Teflon-lined stainless steel reactor (100 ml), hydrothermally treated at 170° C. for 12 h, and then naturally cooled to room temperature.
[0113] 2.3) The solution after the initial reaction was centrifuged at a speed of 11000 rpm / min for 2 h, then washed with deionized water and anhydrous ethanol, and dried. Finally, the dried product was carbonized at 700°C for 30 min under nitrogen protection to obtain a porous silicon sample with pores embedded and surface coated with carbon nanospheres, denoted as Si@C.
[0114] 3) Formation of cyclized polyacrylonitrile coating
[0115] Polyacrylonitrile and Si@C were weighed in a mass ratio of 5:95 and placed in N,N-dimethylformamide solvent, and then stirred in an oil bath at 80°C for 2 hours. The stirred mixture was vacuum dried, ground and other processes were performed, and finally the mixed sample powder was placed in a tubular furnace with argon gas and calcined at 280°C for 1 hour to obtain a porous Si@C sample coated with polyacrylonitrile after cyclization, which was recorded as Si@C-cPAN.
[0116] Comparative Example 1:
[0117] 1) Preparation of porous silicon substrate
[0118] 1.1) The micron-sized silicon powder raw material is subjected to ultrasonic and centrifugal cleaning treatment with deionized water and anhydrous ethanol, and then vacuum dried to remove impurities in the silicon powder.
[0119] 1.2) Prepare 200 mL of a mixed solution containing 0.02 mol / L AgNO3 and 2 mol / L HF, add 2 g of the silicon powder treated in step 1.1) to the mixed solution, react for 3 min under rapid stirring, and then wash with deionized water and vacuum dry to obtain Ag-deposited silicon particles.
[0120] 1.3) Prepare 200 mL of a mixed solution containing 0.05 mol / L H2O2 and 0.15 mol / L HF. Add silicon particles with Ag particles on the surface to the mixed solution, react for 30 minutes, wash with deionized water, and vacuum dry to obtain a porous silicon substrate, denoted as Si.
[0121] Comparative Example 2:
[0122] 1) Preparation of porous silicon substrate
[0123] 1.1) The micron-sized silicon powder raw material is subjected to ultrasonic and centrifugal cleaning treatment with deionized water and anhydrous ethanol, and then vacuum dried to remove impurities in the silicon powder.
[0124] 1.2) Prepare 200 mL of a mixed solution containing 0.02 mol / L AgNO3 and 2 mol / L HF, add 2 g of the silicon powder treated in step 1.1) to the mixed solution, react for 3 min under rapid stirring, and then wash with deionized water and vacuum dry to obtain Ag-deposited silicon particles.
[0125] 1.3) Prepare 200 mL of a mixed solution containing 0.05 mol / L H2O2 and 0.15 mol / L HF. Add silicon particles with Ag particles on the surface to the mixed solution, react for 30 minutes, wash with deionized water, and vacuum dry to obtain a porous silicon substrate, denoted as Si.
[0126] 2) Formation of carbon nanospheres on the surface and in the pores of the porous silicon substrate
[0127] 2.1) Weigh 10 g of glucose and 0.16 g of polyquaternium-11 into 50 mL of deionized water, stir and dissolve at room temperature for 30 min, then add 1 g of the porous silicon substrate prepared in step 1), and continue stirring at room temperature for 2 h.
[0128] 2.2) The mixture obtained in step 2.1) was transferred to a Teflon-lined stainless steel reactor (100 ml), hydrothermally treated at 170° C. for 12 h, and then naturally cooled to room temperature.
[0129] 2.3) The solution after the initial reaction was centrifuged at a speed of 11000 rpm / min for 2 h, then washed with deionized water and anhydrous ethanol, and dried. Finally, the dried product was carbonized at 700°C for 30 min under nitrogen protection to obtain a porous silicon sample with pores embedded and surface coated with carbon nanospheres, denoted as Si@C.
[0130] Comparative Example 3:
[0131] 1) Preparation of porous silicon substrate
[0132] 1.1) The micron-sized silicon powder raw material is subjected to ultrasonic and centrifugal cleaning treatment with deionized water and anhydrous ethanol, and then vacuum dried to remove impurities in the silicon powder.
[0133] 1.2) Prepare 200 mL of a mixed solution containing 0.02 mol / L AgNO3 and 2 mol / L HF, add 2 g of the silicon powder treated in step 1.1) to the mixed solution, react for 3 min under rapid stirring, and then wash with deionized water and vacuum dry to obtain Ag-deposited silicon particles.
[0134] 1.3) Prepare 200 mL of a mixed solution containing 0.05 mol / L H2O2 and 0.15 mol / L HF. Add silicon particles with Ag particles on the surface to the mixed solution, react for 30 minutes, wash with deionized water, and vacuum dry to obtain a porous silicon substrate, denoted as Si.
[0135] 2) Formation of cyclized polyacrylonitrile coating
[0136] Polyacrylonitrile and the porous silicon substrate prepared in step 1) were weighed in a mass ratio of 5:95, and placed in an N,N-dimethylformamide solvent, and then stirred in an oil bath at 80°C for 2 hours. The stirred mixture was subjected to vacuum drying, grinding and other processes. Finally, the mixed sample powder was placed in a tubular furnace with argon gas, and calcined at 280°C for 1 hour to obtain the cyclized polyacrylonitrile-coated porous silicon, which was recorded as Si@cPAN.
[0137] Performance test: The negative electrode materials prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were used to test the negative electrode materials and LiNi 0.9 Co 0.06 Mn 0.04 The O2 positive electrode material was assembled into a CR2025 type button battery, and the cycle performance test and internal resistance test were carried out. The cycle performance test was carried out under the conditions of 2.8-4.2V, 1C, and 25℃. In the internal resistance test, the EIS test frequency was 0.01-100000Hz, the battery SOC state was 100%, and the voltage disturbance was 10mV.
[0138] Test result analysis:
[0139] Table 1 is a summary of the test data of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3.
[0140] Table 1 Summary of electrochemical data
[0141]
[0142] Please refer to Table 1. In the cycle performance test and the internal resistance test, Example 1 performed the best, and Comparative Example 1 performed the worst. This shows that the electrochemical performance of the negative electrode material is significantly improved by providing a conductive carbon material and a coating layer in the pores and on the surface of the porous silicon substrate.
[0143] In the cycle performance test and the internal resistance test, the effect of comparative example 2 is better than that of comparative example 1, but not as good as that of embodiment 1, which indicates that only setting the conductive carbon material in the pores and surface of the porous silicon substrate can improve the electrochemical performance of the negative electrode material, but the effect will be better after setting the coating layer.
[0144] In the cycle performance test and the internal resistance test, the effect of comparative example three is better than that of comparative example one, but not as good as that of embodiment one, which indicates that only setting a coating layer on the surface of the porous silicon substrate can improve the electrochemical performance of the negative electrode material. However, after setting a conductive carbon material in the pores and surface of the porous silicon substrate, the effect will be better.
[0145] Figure 1 The negative electrode material prepared in Example 1 and the negative electrode material prepared in Comparative Example 1 are assembled into CR2025 type buckle batteries, and the capacity retention rate comparison chart after 50 cycles is shown. Figure 1 From the comparison of the capacity retention rate during the medium cycle, it can be seen that the lithium ion battery using the negative electrode material prepared in Example 1 has a good cycle performance, and its capacity retention rate reaches 89.70% after 50 cycles. However, the cycle performance of the lithium ion battery using the negative electrode material prepared in Comparative Example 1 decreases rapidly, and its capacity retention rate is only 56.93% after 50 cycles.
[0146] Figure 2 The negative electrode material prepared in Example 1 and the negative electrode material prepared in Comparative Example 1 are respectively assembled into CR2025 type buckle charging and discharging for 2 weeks. The test frequency is 0.01Hz-100000Hz, the voltage is 4.2V, and the voltage disturbance is 10mV. It can be seen from the figure that the second semicircle of Example 1 is significantly smaller than that of Comparative Example 1, indicating that the charge transfer impedance of the embodiment is lower, indicating that after the porous silicon substrate is modified with conductive materials, the electronic conductivity of the material is enhanced, thereby reducing the lithium ion transfer impedance of the material.
Claims
1. A negative electrode material for a lithium ion battery, characterized in that: The negative electrode material includes a porous matrix, a conductive carbon material and a coating layer from the inside to the outside; Wherein, the material of the porous matrix is silicon or silicon alloy or silicon oxide; the porous matrix includes a plurality of pores, at least part of which are open on the surface of the porous matrix; Part of the conductive carbon material is located on the surface of the porous matrix, and part of the conductive carbon material is located in the pores of the porous matrix; The coating layer has ionic conductivity and / or electronic conductivity, and wraps the entirety of the porous matrix and the conductive carbon material.
2. The negative electrode material of a lithium ion battery according to claim 1, characterized in that The coating layer is in the form of a film or a net.
3. The negative electrode material of a lithium ion battery according to claim 2, characterized in that: The coating layer is in the form of a film, and the material of the coating layer is cyclized polyacrylonitrile.
4. The negative electrode material for a lithium ion battery according to any one of claims 1 to 3, characterized in that: The size of the porous matrix is in the micron level, the pore diameter is greater than 100 nanometers and less than 300 nanometers, and the diameter of the conductive carbon material is less than 100 nanometers.
5. The negative electrode material for a lithium ion battery according to claim 4, characterized in that: The conductive carbon material is carbon nanospheres.
6. A method for preparing a negative electrode material for a lithium ion battery, characterized in that: The following steps are involved: Providing the porous matrix; the porous matrix comprises a plurality of pores, at least part of which are open on the surface of the porous matrix; forming the conductive carbon material on the surface and pores of the porous substrate; The coating layer is wrapped on the surface of the integral structure formed by the porous matrix and the conductive carbon material, and the coating layer has ionic conductivity and / or electronic conductivity.
7. The method for preparing the negative electrode material for a lithium ion battery according to claim 6, characterized in that: The preparation of the conductive carbon material comprises the following steps: Dissolving the carbon source, the structure directing agent, and the dispersant to form a solution; A porous matrix is added to the solution, and the solution is distributed in the pores and surface of the porous matrix; The carbon source in the solution is carbonized under the action of a structure directing agent to generate monodisperse carbon balls; The calcination conditions are controlled to carbonize the carbon balls to form the conductive carbon material.
8. The method for preparing the negative electrode material for a lithium ion battery according to claim 7, characterized in that: The carbon source is one of glucose, maltose, sucrose and soluble starch; The structure directing agent is one of polyquaternary ammonium salt, polymethacrylamide propyl trimethyl ammonium chloride and polydiallyl dimethyl ammonium chloride.
9. The method for preparing the negative electrode material for a lithium ion battery according to claim 6, characterized in that: The porous substrate is a porous silicon substrate, and the formation of the porous silicon substrate comprises the following steps: Micron-sized silicon powder is treated with a mixed solution of AgNO3 and HF to obtain silver-deposited silicon particles; The silicon particles with Ag particles on the surface are treated with a mixed solution of H2O2 and HF to obtain the porous silicon substrate.
10. The method for preparing the negative electrode material for a lithium ion battery according to claim 7, characterized in that: The coating layer is cyclized polyacrylonitrile; the preparation of the coating layer comprises the following steps: placing polyacrylonitrile and the porous matrix containing the conductive carbon material in an N,N-dimethylformamide solvent, heating and stirring to uniformly mix the polyacrylonitrile and the conductive carbon material in the solvent; Afterwards, the mixed solution is post-treated to obtain a mixed powder, and the mixed powder is calcined under the protection of an inert gas to cyclize the polyacrylonitrile, thereby encapsulating the overall structure formed by the conductive carbon material and the porous matrix.
Citation Information
Cited By
Lithium-ion battery negative electrode material and preparation method therefor
WO2026108205A1